Elevated Regulatory T Cell Levels in Glaucoma Patients in Comparison to Healthy Controls. (3rd April 2017) - Bell, Katharina; Holz, Anna; Ludwig, Kirstin; Pfeiffer, Norbert; Grus, Franz H.
ABSTRACT: Background : Many studies analyzing neurodegenerative diseases demonstrate altered frequencies of regulatory T cells (Tregs). Till date, there is hardly any information concerning Tregs in glaucoma. To gather first results concerning Treg levels in glaucoma patients, we aimed to investigate whether the number of CD4(+)CD25(+)T cells vary in the patients suffering from primary open-angle glaucoma (POAG) and healthy controls. Methods : Heparinized blood samples were collected from 16 healthy individuals and 16 POAG patients. The groups were age and gender matched. A density gradient centrifugation over Ficoll-Paque was performed to isolate the peripheral blood mononuclear cells. The resulting cells were stained with fluorescein isithiocyanate (FITC)-conjugated anti-CD4 and phycoerythrin (PE)-conjugated anti-CD25 in single and double staining procedures. Fluorescence-activated cell sorting (FACS) analyses were performed. A total of 200, 000 lymphocytes were gated per measurement based on forward/side scatter. The measurements were performed in triplicate for each sample. Student's t -test was performed. The level of significance was set at p < 0.05. Results were expressed as mean value ± standard error of the mean. Results : We detected a mean percentage of 8.45% CD4(+)CD25(+) T cells of all CD4 (+) T-Lymphocytes in glaucoma patients (standard deviation ± 2.3%). In contrast, a significant smaller percentage of CD4(+)CD25(+) T cells of all CD4 (+) T-Lymphocytes was detected in healthy controls (5.79%; standard deviation ± 1.61%) ( p < 0.01). Conclusion : This study demonstrates increased numbers of CD4(+)CD25(+) T cells in the patients suffering from the neurodegenerative disease glaucoma. Tregs inherit suppressive functions that could be attenuated in glaucoma patients. These results underline the hypothesis of an immunologic involvement in glaucoma via the cellular immunity.